ANALISIS KERAPATAN POPULASI NEMATODA PARASITIK PADA TANAMAN TOMAT (Lycopersicum esculentum Mill.) ASAL KABUPATEN SIGI BIROMARU - Johanes Panggeso (Universitas Tadulako, 2010)
The purpose of this study was to determine the population density of parasitical nematodes on tomatoes. This research used a purposive sampling survey in jonooge and Sidera villages Sigi Biromaru sub district Donggala regency. The research results showed that the nematode population density in jonooge village was 71.00 JI/10 g roots and 63.33 JI/100 g soil whereas in sidera village 43.00 JI/10 g roots and 38.00 JI/100 g soil.